(untitled) (Practicum Psychologia, 2026)
The Nigerian correctional service is grappling with the issue of overcrowding which often makes the control of violence inside prison a difficult task. An overcrowded correctional centre creates a dangerous environment, health hazards and makes it impossible to deliver the defined minimum standards of detention and a near failure to reformation, rehabilitation and reintegration of offenders. Failure of penal institutions to fulfil their correctional obligations has called for action for the criminal justice agencies to make less use of incarceration, develop alternatives, limit pre-trial detention, and treat rather than punish offenders and ensure fairness for all. Incarceration has also shown to be counterproductive in the reduction of recidivism and reintegration of offenders. Reformers therefore seek to reduce penal populations and make increased use of alternatives that are aimed at rehabilitation and reintegration. This is a theoretical paper which examined community sentencing approaches as alternatives to incarceration. The rehabilitative and reparative theories provided theoretical anchorage. The paper showed that community sentencing approaches fulfils all statutory purposes of sentencing, rehabilitates offenders and prepare them for reintegration into the society. The paper concludes that community sentencing approaches are pivotal for the treatment of offenders, provide services to the community and reduce burden on the government and recommends that the Nigerian Correctional Service develop a positive attitude towards non-custodial sentencing and execute further reforms for community sentencing approaches.